Plasma amyloid beta, neurofilament light chain, and total tau in the Systolic Blood Pressure Intervention Trial (SPRINT). Issue 8 (17th November 2021) - Pajewski, Nicholas M.; Elahi, Fanny M.; Tamura, Manjula Kurella; Hinman, Jason D.; Nasrallah, Ilya M.; Ix, Joachim H.; Miller, Lindsay M.; Launer, Lenore J.; Wright, Clinton B.; Supiano, Mark A.; Lerner, Alan J.; Sudduth, Tiffany L.; et al.
Abstract: Introduction: Lowering blood pressure (BP) reduces the risk for cognitive impairment and the progression of cerebral white matter lesions. It is unclear whether hypertension control also influences plasma biomarkers related to Alzheimer's disease and non‐disease‐specific neurodegeneration. Methods: We examined the effect of intensive (< 120 mm Hg) versus standard (< 140 mm Hg) BP control on longitudinal changes in plasma amyloid beta (Aβ)40 and Aβ42, total tau, and neurofilament light chain (NfL) in a subgroup of participants from the Systolic Blood Pressure Intervention Trial (N = 517). Results: Over 3.8 years, there were no significant between‐group differences for Aβ40, Aβ42, Aβ42 /Aβ40, or total tau. Intensive treatment was associated with larger increases in NfL compared to standard treatment. Adjusting for kidney function, but not BP, attenuated the association between intensive treatment and NfL. Discussion: Intensive BP treatment was associated with changes in NfL, which were correlated with changes in kidney function associated with intensive treatment. Trial Registration: clinicaltrials.gov Identifier: NCT01206062